Atenção ao adolescente com uso abusivo de drogas nas políticas públicas de saúde e assistência social no município de Várzea Grande – MT - Amorim, Dulce Regina (2017)
This study aims to analyze the Network of Attention to adolescents with drug abuse in the Municipality of Várzea Grande-MT. The main concern was to know how the actions directed at the attention to adolescents with drug abuse are being implemented in the Health and Social Assistance Policies in said municipality and to verify how the articulation between them is taking place in what is refers to the service to this public. The legal framework that deals with childhood and adolescence, the Federal Constitution, the Statute of the Child and Adolescent, the Organic Law of Assistance and documents referring to the Unified Health System, as well as the official documents of the municipality as a Municipal Plan of the RAPS - Network of Psychosocial Attention and Municipal Plan of the Rights of the Child and the Adolescent.